Elucidating Indonesia’s palm oil supply chain trends: A bibliometric approach - Gunawan, William Ben (Journal of Sustainability, Society, and Eco-Welfare, 2025)
Background: Indonesia’s palm oil supply chain (POSC) plays a critical role in the global economy, contributing over 60% of the world’s crude palm oil (CPO) supply. Despite extensive research on palm oil production and sustainability, there remains a lack of comprehensive bibliometric analysis that maps the evolution of POSC research, identifies key knowledge gaps, and highlights emerging trends. Methods: This study addresses this gap by employing a bibliometric approach to analyze academic research on POSC from 2007 to 2024. Using Scopus data and VOSviewer for visualization, the study identifies key trends, influential authors, research hotspots, and international collaborations. Findings: Results show a significant increase in publications since 2016, driven by global concerns over sustainability, climate change, and the social impacts of palm oil production. Indonesia leads research output, with international collaborations predominantly involving Malaysia and the United States. The findings reveal a shift toward sustainability research, emphasizing environmental challenges, smallholder inclusion, and technological innovations. Conclusion: This study contributes to the literature by providing a systematic mapping of POSC research, highlighting underexplored areas such as supply chain transparency and the role of palm oil in biofuels. Future research should focus on balancing economic development with environmental stewardship and leveraging interdisciplinary approaches to address sustainability challenges. Novelty/Originality of this article: highlights the growing intersection of POSC research with sustainability, technological innovation, and policy development, offering valuable insights for industry stakeholders, policymakers, and researchers.